Implementasi Teknik Komunikasi Dalam Aktivitas Hipnosis Adi W Gunawan - Faridah, Faridah; Masri, Abd. Rasyid; Muhammad, Firdaus; Tajibu, Kamaluddin (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2023)
This study aims to examine communication techniques in Adi W Gunawan's hypnotic activities. This type of research is descriptive with a qualitative approach. Data collection by means of observation, interviews, and documentation, the main data sources are Adi W Gunawan, his assistants, team, trainees, and clients, while the supporting data sources are from relevant articles and books. The collected data is analyzed by reducing data, presenting data, and drawing conclusions. The validity of the research data was carried out by triangulating techniques and sources. The research findings show that one of Adi W Gunawan's hypnotic activities occurred due to the authority and credibility of Adi W Gunawan as chairman of the Indonesian Clinical Hypnotherapy Association (AHKI), an expert in mind technology, completed two doctoral studies, actively participated in training and workshops, trained as a public speaker . Communication in hypnosis activities uses repetitive and imaginative techniques by optimizing verbal and vocal aspects with a higher percentage of visual aspects during therapy, balancing visual, vocal and verbal during training, and highlighting verbal and visual aspects when communicating using media. In this study, researchers also found that in communicating requires empathy, self-confidence, and belief in the heart and mind related to the communication process carried out so that the expected communication goals can be achieved, the researchers call this hypnotic communication or hypnotic communication.